Primary Mucosal Malignant Melanoma of Sinonasal tract: A Case Report Dr. Leena Jain* - Jain, Leena (Journal of Orofacial Research, 2011)
We report the case of primary mucosal malignant melanoma of sinonasal tract in an 45 year old adult male complaining of nasal obstruction and epistaxis, which is very uncommon, presenting with localized disease but with high recurrence rate. We also discuss the principles of management and its outcome.